Prevalência de diagnósticos de enfermagem de incontinência urinária em pacientes com acidente vascular cerebral - Leandro, Telma Alteniza (2015)
This study aimed to identify the prevalence of the nursing diagnoses for Stress urinary incontinence, Urge urinary incontinence, Functional urinary incontinence, Overflow urinary incontinence, and Reflex urinary incontinence in patients with stroke. A cross-sectional study conducted in two public hospitals in Fortaleza-CE, Brazil, from September to November 2013. The sample consisted of 156 patients with diagnosis of stroke. For data collection, we performed interviews with a form designed based on the defining characteristics of the nursing diagnoses. These data were sent to nurse diagnosticians, so they could infer the occurrence of diagnoses for urinary incontinence. We developed a statistical analysis with the SPSS statistical package and adopted a significance level of 7%. Most participants were male, with an average age of 62.28 years, lived with a partner, were retired, and had low education. The most prevalent risk indicators for urinary incontinence, in addition to stroke, were coffee consumption, impaired mobility, hypertension, and diabetes. Among the five diagnoses studied, Overflow urinary incontinence was the most prevalent (72.4%), followed by Functional urinary incontinence (53.2%), Reflex urinary incontinence (50.0%), Urge urinary incontinence (41.0%), and Stress urinary incontinence (37.8%). As regards the diagnosis for Overflow urinary incontinence, the clinical indicators most prevalent were bladder distension and nocturia. Regarding the diagnosis for Functional urinary incontinence, the most prevalent defining characteristics were the urge to urinate and ability to empty the bladder completely. The diagnosis for Reflex urinary incontinence presented a high prevalence of the clinical indicators: inability to inhibit bladder emptying voluntarily, no sense of urgency to empty the bladder, and sense of urgency without voluntary inhibition of bladder contraction. For the diagnosis for Urge urinary incontinence, there was a high prevalence of the defining characteristics: reports of urinary urgency and reports of inability to reach the toilet in time to avoid loss of urine. As for the diagnosis for Stress urinary incontinence, the clinical indicators with significant prevalence were reports of involuntary loss of small amounts of urine when sneezing and coughing. Nursing diagnoses for Stress urinary incontinence, Urge urinary incontinence, Functional urinary incontinence, and Reflex urinary incontinence present statistical associations among them. The diagnosis for Overflow urinary incontinence showed no significant association with the diagnoses for Stress urinary incontinence and Reflex urinary incontinence. With regard to the association of the relevant diagnoses for urinary incontinence with socio-demographic variables, we identified that the age variable had a statistically significant association with Functional urinary incontinence and Overflow urinary incontinence. Thus, we consider that this study provided the diagnosis profile of urinary incontinence of people with stroke and, therefore, may contribute to direct the nursing interventions to specific interventions.